2000
DOI: 10.1161/01.cir.102.23.2867
|View full text |Cite
|
Sign up to set email alerts
|

1α,25-Dihydroxyvitamin D 3 and Its Potent Synthetic Analogs Downregulate Tissue Factor and Upregulate Thrombomodulin Expression in Monocytic Cells, Counteracting the Effects of Tumor Necrosis Factor and Oxidized LDL

Abstract: Because KY3 has the highest affinity for vitamin D receptor, our findings suggest that TF and TM regulation by 1, 25(OH)(2)D(3) analogs is also mediated by vitamin D receptor. The 1, 25(OH)(2)D(3) analogs KY3 and 22-oxacalcitriol may have the potential to serve as an agent for preventing and treating atherosclerotic and other cytokine-mediated thrombotic diseases and as a tool for studying the molecular mechanisms of TF and TM regulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
108
0
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 133 publications
(114 citation statements)
references
References 18 publications
5
108
0
1
Order By: Relevance
“…Further studies are necessary to elucidate the intricate pathways that NF-kB and AP-1 play in TF gene expression. 14 We used 0.1 mM of 1,25(OH) 2 D 3 in this study to reveal the effect on TF expression. The more potent 1,25(OH) 2 D 3 analogs, which have far stronger binding affinity to VDR and which lack an adverse effect of hypercalcemia, have been synthesized.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Further studies are necessary to elucidate the intricate pathways that NF-kB and AP-1 play in TF gene expression. 14 We used 0.1 mM of 1,25(OH) 2 D 3 in this study to reveal the effect on TF expression. The more potent 1,25(OH) 2 D 3 analogs, which have far stronger binding affinity to VDR and which lack an adverse effect of hypercalcemia, have been synthesized.…”
Section: Discussionmentioning
confidence: 99%
“…As the anticoagulant effects of 1,25(OH) 2 D 3 have been detected in monocytic leukemia cell line U937 as well as in human peripheral monocytes, 14 we primarily used monoblastic leukemia cell line THP-1 cells and partly U937 cells in this study, both of which were provided by Health Science Research Bank. Cells were cultured in RPMI-1640 medium supplemented with 10% fetal calf serum, 0.2% sodium carbonate, 2 mM glutamine, and 50 U/ml penicillin-streptomycin.…”
Section: Cell Culturementioning
confidence: 99%
See 2 more Smart Citations
“…Koyama and colleagues (10,12) have found that a hormonally active form of vitamin D, 1␣,25-dihydroxyvitamin D3, as well as retinoic acid, exert anticoagulant effects by up-regulating the expression of the anticoagulant glycoprotein, thrombomodulin (TM), and by down-regulating the expression of a critical coagulation factor, tissue factor (TF), in cultured monocytic cells and human peripheral monocytes. However, it remains unclear whether activation of nuclear VDR can elicit antithrombotic actions in vivo.…”
Section: Vitamin D Metabolites Influence the Expression Of Various Gementioning
confidence: 99%